The application of in situ mid-FTIR fibre-optic reflectance spectroscopy and GC–MS analysis to monitor and evaluate painting cleaning - Kahrim, Kenza; Daveri, Alessia; Rocchi, Paola; de Cesare, Grazia; Cartechini, Laura; Miliani, Costanza; Brunetti, B.G.; Sgamellotti, A. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2009)
The development of non-invasive methodologies and portable instrumentation for in situ studies has been subject to great research and development in recent years in the field of conservation science. Despite such interest, very few reported studies employ these versatile techniques in the monitoring of cleaning treatments. This paper describes the application of mid-FTIR fibre-optic reflectance spectroscopy to monitor and evaluate the cleaning treatment of an oil painting using the chelating agent, triammonium citrate, a task undertaken in close collaboration with the painting conservator. Results obtained on site verify the removal of calcium oxalate and an organic component from the surface of the painting, later identified as a terpenic varnish. The subsequent, in laboratory FTIR and GC–MS analysis of the cotton swabs employed during the cleaning treatment acts as an additional non-invasive manner to support the results obtained in situ by mid-FTIR spectroscopy and to better understand the mechanism of the chosen cleaning agent.